Congenital Megacalycosis with IgA Nephropathy: A Case Report and Review of the Literature. (February 2013) - Turkmen, Ercan; Yildirim, Tolga; Ciftci, Turkmen; Altindal, Mahmut; Akinci, Devrim; Baydar, Dilek Ertoy; Bilen, Cenk Yucel; Arici, Mustafa
<x xml:space="preserve">Abstract</x> Congenital megacalycosis is a rare renal disease characterized by calyceal dilatation without pelvic or ureteral obstruction. If not accompanied by nephrolithiasis and urinary tract infection, this disease is completely benign and does not cause renal dysfunction. We present a case of congenital megacalycosis that was diagnosed at the age of 41 (oldest case in the literature) after admitting with hematuria and acute renal dysfunction. IgA nephropathy was also diagnosed in this patient. Since renal dysfunction is not likely in these patients, if encountered; renal biopsy should be performed although technically difficult to diagnose the cause of this dysfunction.